THE INFLUENCE OF PRODUCTION FACTORS ON THE INCOME OF DAIRY CATTLE FARMERS IN MALANG REGENCY - Stevanus Pati Wedu; Karunia Setyowati; Farida Kusuma Astuti (Universitas Veteran Bangun Nusantara, 2026)
This study aims to analyze the effect of production factors on the income of dairy cattle farmers in Pandesari Village, Pujon Subdistrict, Malang Regency. The research utilized primary data collected through surveys of active dairy farmers and secondary data from relevant institutions. A multiple linear regression method was employed, with independent variables including the number of dairy cows, land area, labor, feed quantity, technology usage, and education level. The results revealed that the number of dairy cows, labor, feed quantity, and technology usage had a significant influence on farmer income (p < 0.05), while land area and education level were not statistically significant. The R² value of 0.673 indicates that 67.3% of the income variation can be explained by the model. These findings highlight the importance of increasing farm scale, labor efficiency, adequate feed supply, and technology adoption to improve dairy farmer income. The study provides valuable insights for policymaking in rural farmer empowerment programs.